Sorong Serah Aji Krama Tradition of Lombok Sasak Marriage to Revive Islamic Culture - Ahyar Ahyar; Subhan Abdullah (el Harakah: Jurnal Budaya Islam, 2019)
Sorong serah aji krama is a tradition of Lombok Sasak tribe community and as a symbol of appreciation in the marriage process of the Sasak tribe community. The symbol of this award is marked by the presence of aji krama. It does not merely have the symbolic meaning of the prospective groom to the bride but implied the symbolic meta meaning. That is, there is a profound meaning of the process of sorong serah aji krama that must be understood, internalized, and implemented in the marriage life of the prospective couple. To that end, this study wants to find the symbolic meta meaning of the tradition of sorong serah aji krama of the Sasak tribe community. This research used descriptive qualitative research. The result shows that the tradition of sorong serah aji krama is not only interpreted as mere preservation of a symbolic material tradition, namely the giving of dowry but also as a meta symbolic of the self-esteem as a human being in the life of the household. The Sasak tribe community views this tradition as the honor and respect of the groom to the bride.Tradisi sorong serah aji krama merupakan tradisi masyarakat suku Sasak Lombok dan sebagai simbol penghargaan dalam proses perkawinan masyarakat suku Sasak. Simbol penghargaan ini ditandai dengan adanya aji krama. Aji krama tidak semata-mata memiliki makna simbolik dari calon mempelai laki-laki kepada mempelai perempuan melainkan tersirat makna meta simbolik. Yakni, ada makna yang mendalam atas proses sorong serah aji krama yang harus dipahami, diinternalisasikan, dan dilaksanakan dalam kehidupan berumah tangga calon mempelai. Untuk itu, penelitian ini ingin menemukan makna meta simbolik tradisi sorong serah aji krama pada masyarakat suku Sasak. Penelitian ini menggunakan penelitian kualitatif deskriptif. Hasil penelitian menemukan bahwa tradisi sorong serah aji krama tidak hanya dimaknai sekedar mempertahankan tradisi yang bersifat material simbolik, yakni pemberian maskawin semata, melainkan dimaknai sebagai meta sombolik akan harga diri sebagai manusia dalam menjalankan kehidupan rumah tangga. Masyarakat suku Sasak memandang tradisi ini sebagai penghargaan dan penghormatan calon mempelai laki-laki kepada mempelai perempuan.